Paham Relativitas Kebenaran Dalam Pluralisme Agama Abdul Karim Soroush - Muhammad Arfan Ahwadzy; Abdurrahman Kafabihi (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2025)
AbstractThe debate on the relativity of truth in religious pluralism, as proposed by Abdul Karim Soroush, has sparked various discussions among academics regarding the relevance and implications of religious pluralism in the contemporary world. Based on this, the present study aims to explore in depth the concept of truth relativity in religious pluralism according to Abdul Karim Soroush using a fiqh approach, in order to provide a broader understanding of the interaction between religious pluralism and fundamental principles in Islamic law. This study employs a library research method with qualitative analysis of Soroush’s thoughts and related literature, as well as a fiqhiyyah approach to examine the relevance of his ideas within the framework of Islamic law. The findings of this study conclude that, according to Abdul Karim Soroush, religious truth is not absolute but rather relative, depending on the context and individual experiences in understanding religious texts. Within the framework of religious pluralism, Soroush emphasizes the importance of recognizing the diversity of religious interpretations that emerge from the different cultural and social backgrounds of humanity. From a fiqh perspective, Soroush’s view on the relativity of truth in religious pluralism contradicts Islamic teachings, which recognize Islam as the only true and absolute religion. Islam teaches that, while goodness can be found in other religions, only Islam brings the ultimate truth for salvation in this world and the hereafter. Misinterpretations of Islamic teachings may foster liberal ideologies that could potentially undermine the faith of the Muslim community. Therefore, the concept of truth relativity as proposed by Soroush risks distorting the understanding of aqidah in Islam and causing confusion regarding fundamental principles of faith. Keywords: Relativity of Truth, Religious Pluralism, Abdul Karim Soroush